Otimização das condições do processo de secagem do extrato de café em leito de espuma e aplicação em mistura para cappuccino - Maciel, Kátia Silva (2017)
As a result of consumers' preference for quality of products and time of preparation, there is an increasing demand related to soluble coffee, both for consumption and as an ingredient in various coffee products, such as cappuccino. In the processing of soluble coffee there are transformations and aromatic losses, that can negatively alter the flavor and aroma of the coffee. Facing such problems, the foam mat is an alternative technology for soluble coffee production. This process is low cost, low temperatures and drying time; in addition, the use of foaming agents allows the formation of a stable foam throughout the drying process, increasing the area exposed to hot air, which the evaporation is facilitated through the spaces filled with air, allowing a greater retention of aromas and compounds, as well as obtaining a porous product with easy rehydration. In this context, the objective of this study was to optimize the conditions of the soluble coffee production process by the foam mat drying method. The experiment was divided into two phases. Initially, the influence of different levels of maltodextrin and whey proteins on the foam production of the coffee extract obtained through the Rotational Central Compound Design were investigated. In the second phase, the effect of different drying air temperatures on the production of dehydrated coffee, was to evaluate, in which the ideal concentration of agents obtained in the previous phase was used. The desirability function was used to define the optimal conditions of the process to obtain powders with the most desirable characteristics in both phases. For this, the following response variables were evaluated: a) related to the coffee extract foam: density and coalescence index; b) related to foam mat drying: drying time; c) related to the powders obtained (dehydrated coffee): solubility, antioxidant activity (DPPH and ABTS), wettability and moisture; d) related to the sensorial analysis of cappuccino: sensorial acceptance. The physicochemical characterization of the obtained powders was performed in relation to water activity, color, pH and acidity. In addition, the study of the drying kinetics of foams was also assessed. Results revealed that the combination of 1.32% maltodextrin and 2.64% whey proteins obtained greater overall desirability (0.6503), since the most desirable characteristics (maximization of flavor acceptance, aroma, the overall impression and antioxidant activity (ABTS and DPPH) and minimization of coalescence index, drying time, wettability and moisture were obtained with this combination. The foam density and solubility of the powders had no influence. In the second phase, the maximum desirability obtained was 0.726 at the drying temperature of 61.77 ºC. The variable sensory acceptance (flavor) was maximized and the variables drying, wettability and moisture were minimized. The different drying temperatures did not influence the variables antioxidant activity (ABTS and DPPH) and solubility. In the physical-chemical characterization of the powders, obtained with different concentrations of agents, there was an influence on the variables color, pH, acidity and water activity. In the powders obtained at different temperatures, a significant difference occurred only in the water activity response variable. It is concluded that the foam formation with 1.32% maltodextrin and 2.64% whey proteins, using the temperature of 61.77 oC for drying, are the optimal conditions for the drying process of the extract coffee in foam mat.